2020
DOI: 10.1016/j.jvs.2019.07.102
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative adverse events and early outcomes of custom-made fenestrated stent grafts and physician-modified stent grafts for complex aortic aneurysms

Abstract: Objective: Physician-modified fenestrated stent grafts (PMSGs) are a useful option for urgent or semiurgent treatment of complex abdominal aortic aneurysms (CAAAs). The aim of this study was to describe in-hospital outcomes of custommade fenestrated stent grafts (CMSGs) and PMSGs for the treatment of CAAAs and thoracoabdominal aortic aneurysms (TAAAs).Methods: In this single-center, retrospective study, all consecutives patients with CAAAs or TAAAs undergoing endovascular repair using Zenith CMSGs (Cook Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…A recent article shows how, in complex aortic aneurysm, clinically relevant differences of several important in-hospital outcomes were found in the use of custom made stent grafts versus physician-modified fenestrated grafts. 8 The combined one step endovascular and surgical procedure is not a new concept and is being practiced in different settings, especially when emergency intervention is required where the vascular anatomy and/or clinical conditions are not favorable for any of the options alone. 9 …”
Section: Discussionmentioning
confidence: 99%
“…A recent article shows how, in complex aortic aneurysm, clinically relevant differences of several important in-hospital outcomes were found in the use of custom made stent grafts versus physician-modified fenestrated grafts. 8 The combined one step endovascular and surgical procedure is not a new concept and is being practiced in different settings, especially when emergency intervention is required where the vascular anatomy and/or clinical conditions are not favorable for any of the options alone. 9 …”
Section: Discussionmentioning
confidence: 99%
“…3,8 In a previous systematic review of 23 reports containing 308 patients treated between 1999 and 2015 for complex aortic aneurysm, outcomes overall were similar for off-the-shelf fenestrated/branched stent-grafts and PMEGs, including technical success of 95% and 91%, mortality of 1.1% vs 3.5%, and target vessel patency of 98% vs 97%, respectively. 9 Since that review, many additional studies (those with ≥10 cases) citing the use of PMEGs have been published, [1][2][3][4][5]7,8,[10][11][12][13][14][15] though some updated earlier populations within investigation device exemption (IDE) protocols 2,3,13 or earlier single-center reports. 4,5,7,10 Excluding 4 duplicate studies (103 cases) 8,[13][14][15] and another 101 patients presented earlier, 9 375 new cases not incorporated in the previous review were identified since March 31, 2015 (a 100% increase), even though in some qualified centers the use of PMEGs declined from 66% between 2011 and 2013 to 4% between 2014 and 2016.…”
Section: Pmegsmentioning
confidence: 99%
“…Overall, 9 additional single-center studies were found (Table 1), [1][2][3][4][5]7,[10][11][12] 3 of them conducted within an IDE trial, 2,3,12 with a total of 476 patients (339 men, 71.2%). Few of these compared outcomes between PMEGs and company-manufactured devices 3,5,7 and hybrid techniques. 1 The latter comparison is what the study by Yang et al 1 adds to the literature.…”
Section: Pmegsmentioning
confidence: 99%
See 2 more Smart Citations